1997
DOI: 10.1136/adc.77.3.219
|View full text |Cite
|
Sign up to set email alerts
|

Educational progress, behaviour, and motor skills at 10 years in early treated congenital hypothyroidism

Abstract: Aim-To assess educational attainments, behaviour, and motor skills at 10 years of age in a group of children with congenital hypothyroidism identified by neonatal screening. Results-On all measures the congenital hypothyroidism children in group I had less satisfactory scores for educational attainments, behaviour, and motor skills than those in group II and controls. For reading the diVerences were small and did not reach statistical significance, but the deficits in mathematics and total motor skills were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 15 publications
1
29
1
3
Order By: Relevance
“…In the limited literature discussing these higher order cognitive skills, children and adolescents with CH are described as deficient in memory [2][3][4] and attention [5][6][7] compared to controls. More behavioural problems were found in terms of activity regulation 8 and internalising symptoms, 9 while one study reported no significant group differences. 3 To our knowledge, adult outcome studies have not been reported.…”
mentioning
confidence: 93%
“…In the limited literature discussing these higher order cognitive skills, children and adolescents with CH are described as deficient in memory [2][3][4] and attention [5][6][7] compared to controls. More behavioural problems were found in terms of activity regulation 8 and internalising symptoms, 9 while one study reported no significant group differences. 3 To our knowledge, adult outcome studies have not been reported.…”
mentioning
confidence: 93%
“…However, Rovet et al (20) reported mild non-verbal learning disability in some children with CH. Recently, less satisfactory scores for educational attainments, behaviour and motor skills were reported in CH children with more severe neonatal hypothyroidism (T 4 Յ 3 mg/dl, 40 nmol/l) compared with less affected CH children (neonatal T 4 > 3 mg/dl, 40 nmol/l) (21). While differences for reading were small, deficits in mathematics were statistically significant (21).…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of school attainments in CH children treated early in life have produced controversial results (19,20). School performances were found normal by the New England Congenital Hypothyroidism Collaborative (19), but mild non-verbal learning disability (20) and mild impairment in educational attainments (21) have been found in other series of early treated CH children.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed from the three Speechlanguage Pathology fields investigated, language was the one with higher number of published papers [16][17][18][19][20][21][22][23][24][25][26] . This allows the arguing about this topic in CH children to be more clear and consistent, but do not exclude the importance of other communication aspects.…”
Section: Methodsmentioning
confidence: 99%
“…Subtitles: SG= study group; CG = control group Figure 2 -Contents of localized papers about speech-language disturbances related to congenital hypothyroidism significant delay in language development [17][18][19][20][22][23][24]26 .…”
Section: Michelsson Et Al;1976 25mentioning
confidence: 99%